2018
DOI: 10.1186/s40360-018-0264-8
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib: Evidence review and clinical practice in the management of advanced renal cell carcinoma

Abstract: BackgroundPazopanib is indicated in the first-line treatment of metastatic renal cell cancer (mRCC). The aim of this study was to review the efficacy, safety, and pharmacokinetics of pazopanib and see how these aspects are linked to clinical practice.MethodsA non-exhaustive systematic review was conducted according to the three topics. No publication restrictions were imposed and the selected languages were Spanish and English. After that, a summary of the main results and findings of the review was presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 73 publications
(89 reference statements)
3
15
0
2
Order By: Relevance
“…Compared to the low-risk group, patients in the high-risk group had higher TIDE scores, suggesting that patients in the high-risk group may have a more limited response to ICI therapy. Previous clinical trials have confirmed that the benefits of pazopanib are more prominent in the low-risk group, which is consistent with our study (Méndez-Vidal et al, 2018). However, in the case of sorafenib, there is no evidence in the literature that it is more beneficial in the high-risk group, and the exact mechanism remains to be confirmed by more studies.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to the low-risk group, patients in the high-risk group had higher TIDE scores, suggesting that patients in the high-risk group may have a more limited response to ICI therapy. Previous clinical trials have confirmed that the benefits of pazopanib are more prominent in the low-risk group, which is consistent with our study (Méndez-Vidal et al, 2018). However, in the case of sorafenib, there is no evidence in the literature that it is more beneficial in the high-risk group, and the exact mechanism remains to be confirmed by more studies.…”
Section: Discussionsupporting
confidence: 91%
“…With the understanding of molecular biology of RCC, several targeted agents inhibiting VEGF and mTOR signal transduction pathways such as Sunitinib, Sorafenib, Temsirolimus, and Pazopanib have been put into clinical practice. [33][34][35][36] Meanwhile, statistical results in our study revealed that targeted therapy significantly prolonged the OS of patients with spinal metastasis from CCRCC. Increasing clinical evidence has proven that targeted therapy can downsize the tumor size, control tumor progression, and improve OS, in view of Sunitinib and Sorafenib as the first-line or second-line treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Pazopanib is a multi-kinase inhibitor medication indicated as a first-line treatment for adult patients with metastatic renal cell carcinoma (RCC). 1 It targets the vascular endothelial growth factor receptor, c-kit protein, and the platelet-derived growth factor receptor. Additionally, it strongly inhibits angiogenesis.…”
Section: Introductionmentioning
confidence: 99%